Notes on “Dharma Buddha’s Body” (Dharmakāya) in the Context of AbhisamayālaṅkāraРrajñа̄ра̄ramitā-Uраdеśа-Śа̄stra - Коробов, Владимир (Acta Orientalia Vilnensia, 2003)
The paper focuses on Mahayana Buddhism conception of “Buddha’s bodies” as it is presented in Abhisamayālaṅkāraрrajñа̄ра̄ramitā-uраdеśа-śа̄stra and its interpretations by different Indian and Tibetan commentators. Mahāyana conception of three Buddha’s bodies in its connection to five transcendental wisdoms is analyzed on the basis of traditional commentaries of different Buddhist scholars (Sthiramati, Śilabhadra, Haribhadra, Buddhadjñanapada).The analysis of the conception of Buddha’s body conception in Mahāyana Buddhism provides with an opportunity to apprehend a conception of Mahāyanist Nirvāṇa, which is the state beyond all definitions, discriminations and goals. Apophatic paradoxical goal in Mahāyana Buddhism from the very beginning implies renunciation of all hopes, tasks and results. No goals may be reached on this path, everything is useless, but this uselessness uncovers itself as a real representation of suchness and emptiness.